Intensification and anti-erosion measures in Southern Mali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Only by intensifying agricultural production systems will there be any chance of curbing erosion and its effects in the Sahel. Intensification involves limiting the area of cultivation, and maintaining, if not restoring, soil fertility by the use of...